Projected Climate Indices Impact on the Hydrological Process in the Bago River Basin, Myanmar - Suwai Thin; Koichiro Ohgushi (International Association of Lowland Technology, 2023)
Despite the impact of temperature and precipitation patterns on river flow is an emerging issue in hydrology, few studies have been concentrated on the correlation between the hydrological components and climate indices. This study mainly focuses on the projected extreme climate indices and the effects of climate change projections on the hydrological process in the Bago River Basin, Myanmar. It has been noted that the mean monthly maximum temperature values are expected to rise throughout the entire basin under the RCP 4.5 scenario. On the other hand, the annual total precipitation index is anticipated to increase. The findings imply that the groundwater and surface flow will eventually expand as a result of the effects of extreme precipitation indices. Subsequently, there will be a decrease in the lateral flow. Furthermore, it is observed that the effect of temperature indices will cause a significant impact on evapotranspiration. This paper highlights that the crucial part of the extreme climate indices that influence the regional hydrological processes of the Bago River Basin in the upcoming decades.